The influence of exposure to pesticides on the development of depression: a systematic review (Research, Society and Development, 2021)
The growth of the world population has increased the demand for food and required large-scale food production through the use of numerous agricultural practices, such as the use of pesticides in crops to eliminate pests and ensure productivity. However, the consequences of using these products and their repercussions on human health have been the subject of discussion in academia. Objective: identify the impacts of pesticides on mental health. Methodology: this is a study with a descriptive-analytical-reflective approach. Studies published between the years 2011 and 2020 were selected from the following databases: National Library of Medicine (PubMed), Virtual Health Library (VHL) and Scientific Electronic Library (SciELO). The descriptors in English and Portuguese were used: Agrotoxic OR Agrochemicals AND Depression OR Depression AND “Drinking Water” OR “Drinking Water” AND/OR Alimentos OR Food. Inclusion criteria: scientific articles with Qualis Capes in Public Health above B3; course completion works at master's and doctoral level. Results: Eleven studies were selected that showed a cause-effect relationship between human exposure to pesticides and damage to mental health, such as: depression, cognitive decline, anxiety, fatigue, emotional imbalance. Conclusion: Studies show that the use of pesticides has affected human health. The importance of awareness of the use of Personal Protective Equipment (PPE) and the correct disposal of packaging for these products is highlighted. It is suggested the development of researches that point out more sustainable agricultural strategies to replace chemical pesticides, such as the use of biopesticides.